Artificial Intelligence in Natural Resources Management: Selected Case Studies from Africa - Musonda Kapatamoyo (International Telecommunications Society (ITS), 2024)
This paper explores Artificial Intelligence (AI) 's transformative role in digital transformation and its implications for Africa's socio-economic development. We examine how AI's advanced analytics, machine learning algorithms, and predictive modeling capabilities reshape operational strategies. Case studies elucidate the diverse applications of AI in Africa, including natural resource management such as mining, wildlife conservation, precision agriculture, and water resource management. Examples such as copper deposit discovery in Zambia (Mitimingi & Hill, 2024) and AI-powered wildlife monitoring in Burkina Faso (Vermeulen et al., 2013) illustrate its potential to drive growth, competitiveness, and sustainability across the continent.
Keywords: 330